Hybrid Sterility, Genetic Conflict and Complex Speciation: Lessons From the Drosophila simulans Clade Species - Presgraves, Daven C.; Meiklejohn, Colin D. (Frontiers in Genetics, 2021)
The three fruitfly species of the Drosophila simulans clade— D. simulans, D. mauritiana, and D. sechellia— have served as important models in speciation genetics for 40 years. These species are reproductively isolated by geography, ecology, sexual signals, postmating-prezygotic interactions, and postzygotic genetic incompatibilities. The close phylogenetic proximity of the D. simulans clade species to the more distantly related model organism, D. melanogaster, has empowered genetic analyses of their reproductive incompatibilities and other species differences. Perhaps no other phenotype among these species has been subject to more continuous and intensive genetic scrutiny than hybrid male sterility. All pairwise crosses between these species conform to Haldane’s rule, producing fertile F1 hybrid females and sterile F1 hybrid males. Haldane’s rule stands as one of the strongest patterns to characterize speciation but its genetic and evolutionary causes remain elusive. Here we review the history, progress, and current state of our understanding of hybrid sterility in the D. simulans clade species. Using these species, our aim is to integrate information from functional genetics and population genomics analyses to make inferences about the causes and consequences of hybrid sterility. We highlight the numerous conclusions that have emerged as well as issues that remain unresolved. In particular, we present the evidence that sex chromosomes play a disproportionately large role in speciation, that the genetic basis of hybrid male sterility is complex, and that the history of speciation among these geographically allopatric taxa nevertheless involves gene flow. The biggest surprises to emerge from this work are that (i) genetic conflicts may be an important force in the evolution of hybrid incompatibility, (ii) hybrid sterility is highly polygenic, and (iii) speciation has involved the interplay of gene flow, negative selection, and positive selection. These conclusions are marked departures from classical views of speciation that emerged from the modern evolutionary synthesis.